Tinjauan Al-Quran dan Hadist Tentang Sifat-Sifat Pemimpin (Studi Literatur) - Rusmita, Rusmita; Siskawati , Oies Febria; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to explore verses and hadiths related to the characteristics of leaders, outline their implications in a modern context, and provide an in-depth understanding of how these principles can be applied in the effective management of Islamic educational institutions. This study uses a qualitative approach with a literature study method. The main data of this study comes from books and articles published on google scholar. Data collection was carried out using the keywords